Effect of Absorptivity of Superabsorbent Polymers on Design of Cement Mortars - Fořt, Jan; Migas, Przemysław; Černý, Robert (Materials (Basel, Switzerland), 2020)
The functional properties of composites modified by superabsorbent polymers (SAPs) strongly depend on the swelling capacity of applied SAPs. In this sense, three types of commercially available SAPs namely Cablock CT, Hydropam, and Creasorb SIS with different chemical composition and particle size distribution were studied in this manuscript to reveal the differences in absorptivity as can be viewed as pretests for their utilization in concrete composites. In addition, absorptivity in distilled water, tap water, and 0.1 M NaCl solution are examined for determining the SAPs response for the change of the solution pH. To overcome problems with the teabag method inaccuracy, the new method is introduced. Besides to quantitative evaluation of the SAPs absorptivity, the correlation for the absorption and desorption period as the function of SAPs residence time within the examined solution is proposed. To access the effect of selected SAPs on functional properties, optimization based on the flow table test is employed and mechanical parameters are determined after 7, 14, 28, and 90 days of curing. Obtained results refer to substantial differences between particular SAPs and contribute to the understanding of the effect of SAP on the functional properties of cement-based materials.
Keywords: absorptivity; filtration method; teabag method; superabsorbent polymer (SAP); flow table test; mechanical performance